Evaluation of Softwoods viz., Cupressus lusitanica, Pinus radiata and Pinus patula for Paper Making - Moorthy, V. L.; Guha, S. R. D.; Sharma, Y. K.; Mathur, G. M. (Indian Forester, 1977)
Laboratory scale, pilot plant acale and mill sCale trials on mixtures of three conifers viz., Cupressus lusilanica, Pinus patula and Pinus radiata grown in Kenya have been deacribed. The fibre length or the pulps were 1.90 mm., 3.05 mm and 2.82 mm respectively for C. lusitanica, P. radiala and p. patula. Pulps in satisfactory yield and strength properties should be prepared by the species separately as well as in lower tearing strength then the other species. Bleachability or pulps were good. Pilot plant scale trials and mill scale trials confirmed the laboratory results.